2019
DOI: 10.1007/s12072-019-09977-w
|View full text |Cite
|
Sign up to set email alerts
|

Wnt status-dependent oncogenic role of BCL9 and BCL9L in hepatocellular carcinoma

Abstract: Background Activation of Wnt/β-catenin pathway is a frequent event in hepatocellular carcinoma and is associated with enhanced cell survival and proliferation. Therefore, targeting this signaling pathway is discussed as an attractive therapeutic approach for HCC treatment. BCL9 and BCL9L, two homologous coactivators of the β-catenin transcription factor complex, have not yet been comprehensively characterized in HCC. We aimed to elucidate the roles of BCL9 and BCL9L, especially regarding Wnt/β-catenin signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 26 publications
(42 reference statements)
2
26
0
Order By: Relevance
“…The reduced expression of Mettl3 and Ki67 with the increased level of Caspase-3 was detected by randomized double-blind IHC scoring in Upk3a CreER ; Mettl3 flox/flox mice, manifesting the role of Mettl3 in promoting proliferation and inhibiting apoptosis in vivo ( Figure 1F ). A significant reduction in AKT1 (a proliferation-related factor) ( Wang et al, 2019 ) and BCL9L (an inhibitor of apoptosis) ( Huge et al, 2020 ) was observed by the loss of Mettl3 in Upk3a + BCa cells ( Figure 1G ). These results indicate that Mettl3 is essential for cellular proliferation and survival in BBN-induced BCa.…”
Section: Resultsmentioning
confidence: 99%
“…The reduced expression of Mettl3 and Ki67 with the increased level of Caspase-3 was detected by randomized double-blind IHC scoring in Upk3a CreER ; Mettl3 flox/flox mice, manifesting the role of Mettl3 in promoting proliferation and inhibiting apoptosis in vivo ( Figure 1F ). A significant reduction in AKT1 (a proliferation-related factor) ( Wang et al, 2019 ) and BCL9L (an inhibitor of apoptosis) ( Huge et al, 2020 ) was observed by the loss of Mettl3 in Upk3a + BCa cells ( Figure 1G ). These results indicate that Mettl3 is essential for cellular proliferation and survival in BBN-induced BCa.…”
Section: Resultsmentioning
confidence: 99%
“…B-Cell Lymphoma 9-Like Protein (BCL9L), as a cofactor for canonical Wnt signaling, is a component of BCL9 family and mediates EMT ( Gay et al, 2019 ). It has been reported that BCL9L induces early phases of human intestinal cancer progress by regulating the β-catenin function switch between adhesion and transcription ( Brembeck et al, 2004 ; Huge et al, 2020 ). Moreover, BCL9L is demonstrated to enhance β-catenin–mediated transcriptions and increase the abilities of proliferation and metastasis in breast and colon cancer cell lines ( Brembeck et al, 2011 ; El-Hage et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, simultaneously BCL9/BCL9L depletion completely suppresses β-Catenin driven intestinal and hepatocellular transformation in mouse models 39 . BCL9L overexpression is positively correlated with poor overall survival in hepatocellular carcinoma patients, and silencing BCL9L, but not BCL9, reduced Wnt signaling, and suppressed cell growth and induced apoptosis of Wnt-inactive hepatocellular carcinoma cells 40 . In pancreatic cancer, BCL9L knockdown decreases cell proliferation, migration, invasion, and liver metastasis, and increases E-cadherin expression even in the presence of TGF-β, suggesting a role of BCL9L in regulating EMT 31 .…”
Section: Discussionmentioning
confidence: 96%